A Review of Inclusive Design and Multisensory Interactions Studies and Applications in Public Spaces. Issue 1 (1st December 2022) - Boucherit, S; Berkouk, D; Bouzir, TAK; Masullo, M; Maffei, L
Abstract: Inclusive design (ID) is one of the innovative strategies contributing to understanding public spaces designed for occupants' diversity and needs. This paper aims to provide an overview of the importance, procedure, and future scope for evaluating multisensory interactions while applying ID principles. Through this work, it is possible to move the knowledge forward to participate and fill the scientific gap related to the two concepts of multisensory perception and inclusive design in public spaces for all the people with special needs concentrating on visually impaired people. The focus of this paper is organized into three parts discussing both concepts: (1) a thorough review of the literature from 2002 to 2022; (2) a review of data collection and processing techniques; and (3) a review of the research studies motivations, implications, and its future scopes and applications.